Livelihood diversification and welfare of rural households in Ondo State, Nigeria (2013)
Agriculture, the main source of livelihood in Nigeria, especially in the rural areas, is plagued with various problems. As a result, most of the rural households are poor and are beginning to diversify their livelihoods into off and non-farm activities as a relevant source of income. This study examined the effect of livelihood diversification on the welfare of rural households in Ondo State. Primary data used in the study were obtained from 143 respondents selected employing a multistage sampling technique. Data were analyzed using descriptive statistics, multinomial logit and the logit regression models. The distribution of respondents by the type of livelihood strategy adopted revealed that almost three-quarters of the respondents adopted the combination of farm and nonfarm strategy. Econometric analysis showed that household size, total household income and primary education of the household head were the dominant factors influencing the choice of livelihood strategies adopted. Income from non-farm activities, as well as income from a combination of non-farm and farming activities, impacted welfare positively relative to income from farming activities. The study recommends the promotion of non-farm employment as a good strategy for supplementing the income of farmers as well as sustaining equitable rural growth.